Routine transfusion of platelet concentrates effectively reduces reoperation rate for bleeding and pericardial effusion after elective operations for ascending aortic aneurysm. (16th November 2016) - Perek, Bartłomiej; Stefaniak, Sebastian; Komosa, Anna; Perek, Anna; Katyńska, Izabela; Jemielity, Marek
Abstract: Patients with ascending aortic aneurysm undergoing complex surgical procedures are at increased risk of early postoperative excessive blood loss. The aim of this study was to analyze safety and efficacy of routine transfusions of platelet (PLT) concentrates in reduction of hemorrhagic postoperative complications. The study involved 396 consecutive patients (289 males and 107 females) with the mean age of 55.9 ± 13.6 years who underwent elective operations for aortic aneurysms. They were divided retrospectively into two groups, without (group A; n = 123) or with the routine use of PLTs (group B; n = 273). PLTs were transfused intraoperatively just after completion of cardiopulmonary bypass. Twelve patients in group A (9.8%) and 10 (3.7%) in group B required re-thoracotomy due to hemorrhage ( p = 0.027). Routine transfusions of PLT concentrates reduced postoperative incidence of excessive pericardial effusion from 24.1% in group A to 2.1% in group B ( p = 0.002). In a consequence, significantly less units ( p < 0.0001) of red blood concentrates and fresh frozen plasma were transfused in group B than in group A. The rates of other adverse events in the early postoperative period did not differ between groups. Patients with pericardial effusion required 6.3 ± 2.7 additional days of hospitalization due to surgical re-intervention. Neither blood transfusion-related infections nor adverse reactions were noted. In conclusion, routine intraoperative transfusions of PLT concentrates in patients with ascending aortic aneurysms significantly reduced a need for re-intervention due to both early bleeding and late cardiac tamponade.